Attitudes of Sport Science Students Regarding to Gender Roles - Malkoc, Nedim (Asian Journal of Education and Training, 2020)
Social gender is the difference that gender creates in a society, it is related to how one thinks of him or herself, how him or her interacts with others, social opportunities, professions, family roles, and the roles allowed for men and women. There is pluralist participation and a sense of justice in the philosophy of sports. In this context, all stakeholders (athletes, coaches, assistants, etc.) involved in sports activities are expected to evaluate and interpret sports activities in this context. The research was carried out using quantitative research method. A total of 318 students from the School of Physical Education and Sports (fourth grade) of Kastamonu University participated in the study. Perception Gender Scale consisting of 1 dimensions and 25 items, created by Altinova and Duyan (2013) was used as measurement tool. High average score of the scale indicates the positive perception of society gender roles. The data were found to be normally distributed and parametric test methods were used. According to results of the research conducted, the perceptions of gender of sports science students are at a medium level. In addition, gender perceptions of female sports science students were differentiated from male sports science students. The perceptions of gender did not differ among sports science students within the scope of the departments they received education. In addition, a low level of negative correlation was found between the ages of sports science students and their gender perceptions.